A Systematic Review of The Efficacy of Korean Ginseng in Men with Erectile Dysfunction - Rayi Megasari Putri; Aucky Hinting; Primasitha Maharani Harsoyo; Fiosanda Rizky Nugrahanti (Indonesian Andrology and Biomedical Journal, 2023)
Erectile dysfunction (ED) is a common condition that has a substantial impact on quality of life. It is described as the continuous inability to develop or maintain sufficient stiffness of the penis to allow satisfactory sexual performance. Early detection and treatment of ED and comorbidities associated with ED, such as hypertension, diabetes mellitus, and hyperlipidemia, can significantly improve the quality of life for men and their partners. About 35.6% of Indonesian adults have ED. The bulk of ED treatments now on the market are pharmacological and surgical procedures. Even though there has been substantial progress, it seems that the aforementioned treatment has a high dropout rate due to cultural restrictions and taboos. These patients would then look for herbal nutritional supplements like ginseng as an alternative. This systematic review evaluates the current evidence for the effectiveness of red ginseng in managing erectile dysfunction. We performed systematic review conducted from MEDLINE, ScienceDirect, ProQuest. The authors screened the articles based on inclusion criteria : (1) Mild-to-moderate erectile dysfunction; (2) Ginseng as interventional therapy; (3) Human studies that have IIEF score as an outcome; (4) Written in English. Four randomized control trials (RCT) using keywords “((Erectile Dysfunction) AND (Korean Ginseng) AND (Ginseng))” were included. Three randomized control trials (RCT) study involving 454 male patients with mild to moderate erectile dysfunction, aged from 20 to 70 years old. Our findings support that the mean in International Index of Erectile Function scores were significantly higher in patients treated with Korean ginseng than in those who received placebo. Korean ginseng could be an effective alternative treatment for male erectile dysfunction if more research with larger-scale clinical trials and higher standards is done in the future on the safety and effectiveness of ginseng.